De travers dans la gorge : l'impact du coronavirus sur la musique traditionnelle au Québec - Gauthier, Antoine (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Antoine Gauthier, Director of the Conseil québécois du patrimoine vivant (CQPV), an umbrella organization of over 100 intangible cultural heritage organizations from across Québec, describes the impact of the pandemic on the traditional arts in that province.